From Similarities to Singularity: the common fate dimensions and toolkit for cities of tomorrow: من التشابه إلى الانفراد: أبعاد وأدوات المصير المشترك لمدينة الغد - Hisham G. Abusaada (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
This article examines the common fate of the three concepts that interprets the sameness of cities. It begins with a concise exploration of “personality”, “identity” and “character” in terms of the dual singularity—difference and similarity—of cities. Whatever, there is still a significant overlap between the meaning of identity and character, which threatens to weaken both concepts. This research addresses two aspects. The first is the dimensions of the common ground between personality, identity, and character. The second explores these two dimensions in the conventional and the contemporary prospects concepts in the Western paradigms to create the cities of tomorrow for offering the toolkit of singularity. The main conclusion highlights the question is: What should be examined to produce cities that are not alike in the future? Ultimately, there is scope to further strengthen singularity- based planning and design approaches through a toolkit help specialists to dominate the sameness of cities.